Model Modernisasi Pendidikan Islam di Indonesia - Muhammad Heriyudanta (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2022)
This paper intends to research and see how the development of modern Islamic education in the modern Islamic boarding school Darussalam Gontor, Ponorogo, East Java. This type of research is library research. The data is taken from various sources of scientific literature such as books, journals, and various types of scientific works that are relevant to the research study. While the approach uses a philosophical approach. The data collection techniques used documentation techniques, then analyzed using content analysis data analysis methods. In this study, it was found that the modernization breakthrough taken by the modern Islamic boarding school Darussalam Gontor was in two forms. First, in terms of the management and management of the institution, and the second in terms of modernizing the curriculum. The management of Gontor Islamic Boarding School by waqf is intended so that the pesantren can grow more advanced, be more open, and have no shortage of future generations. While the curriculum is modernized according to the needs of human nature itself as well as according to the needs of the times. This is marked by the provision of subject matter that teaches 100% general science and 100% religious knowledge, special emphasis on aspects of mastering foreign languages, and quite complete extracurricular facilities such as skills, sports, and arts. Therefore, the modern Islamic education development model developed by the modern Darussalam Gontor Islamic boarding school is worthy of being used as a pilot project in an effort to develop Islamic education in the contemporary era. Keywords: Model, Modernisation, Islamic Education.